The Impact of Training and Career Development on Employee Retention at the North Wara Health Center - Jusnita; Indra Kusdarianto; Dirham (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the impact of training and career development on employee retention at Wara Utara Public Health Center (Puskesmas). A quantitative research method with a survey approach was employed. Data were collected through questionnaires distributed to 44 respondents, comprising both medical and non-medical staff. Multiple linear regression analysis was used to examine the relationship between the independent variables training (X1) and career development (X2) and the dependent variable, employee retention (Y). The findings indicate that career development has a significant effect on employee retention, with a regression coefficient of 0.651 and a significance level of 0.015 (<0.05). In contrast, training has a positive but statistically insignificant effect, with a regression coefficient of 0.287 and a significance level of 0.282 (>0.05). Simultaneously, training and career development significantly contribute to employee retention, as evidenced by an F value of 86.682 and a significance level of 0.000. The coefficient of determination (R²) is 0.809, indicating that 80.9% of the variation in employee retention can be explained by training and career development. These results suggest that structured career development programs contribute more significantly to enhancing employee loyalty compared to training programs. Therefore, organizations are encouraged to strengthen career development strategies to improve employee retention and reduce turnover rates.